Aditivos na conservação de CMS e estabilidade de empanados de pacu de tanques-rede do Pantanal - Zuanazzi, Jovana Silva Garbelini (2013)
This study is divided into two scientific articles. The first article was to evaluate the mechanically deboned meat of pacu (CMS) with addition of sodium erythorbate and sodium tripolyphosphate and verifying some of its properties physical and chemical in intervals of 0, 30, 60, 90 and 120 days of storage at -18 °C. The second article it is the preparation of breaded from the CMS of pacu, evaluating the parameters physical, chemical, microbiological and sensory in the intervals of 0, 30, 60, 90 and 120 days of storage at -18°C. The samples of mechanically separated meat were divided into four treatments verifying its stability over the months. The data were analyzed to determine pH, color, water-holding capacity (CRA), myofibrillar fragmentation index (IFM), water activity (Aw) and chemical composition in four different treatments using sodium 0.1% of erythorbate + 0.5% of sodium tripolyphosphate, 0.1% of sodium erythorbate, 0.5% of sodium tripolyphosphate, and no additives. The breaded were prepared according to specific wording and subject to the microbiological, physical and chemical properties and sensory. It is concluded that addition of sodium erythorbate increased significantly Aw, CRA and the IFM by the thirtieth day of storage. The addition of tripolyphosphate had an influence on pH and CRA which remained stable for longer the first parameter and reduced tendency to decrease the value of the second. The storage time influenced differently the parameters analyzed. The Aw and the L* value decreases suffered the greatest at the beginning of storage, while the IFM and CRA tended to decrease continuously over time. The combined use of sodium erythorbate and sodium tripolyphosphate was the most efficient, since promoted the desirable increase in CRA while other treatments tended to decrease the value of this parameter. The lipid oxidation in breaded CMS pacu stored at -18 °C was low, indicating no rate of rancidity in the product. The results of the microbiological analysis of the breaded CMS pacu are the standards set by law; it reflects that the handling of raw materials to the final product was performed adequately for human consumption. The sensory evaluation of breaded of pacu CMS indicated good acceptance by the tasters, where more than 32% would buy the product frequentily.